Athlete body composition influences movement during sporting tasks: an analysis of softball pitchers' joint angular velocities. - Friesen, Kenzie B.; Aguinaldo, Arnel; Oliver, Gretchen D. (Sports Biomechanics, 2024)
Softball pitchers are often above-average size and frequently injured; therefore, it is necessary to understand how biomechanics can change according to pitcher body composition. The purpose of this study was to examine the relationship between joint peak angular velocities and pitch velocity, as well as examine how pitchers' joint angular velocities differ between high and healthy body-fat percentage (BF%) groups. Forty high-school and college softball pitchers (170.6 ± 6.3 cm, 75.5 ± 16.1 kg, 16 ± 2 years, 34.6 ± 7.4 BF%) completed body composition testing and were placed in one of two groups: 1) high-fat% (≥32%) or 2) healthy-fat% (<32%). Pitchers completed fastball trials. Kinematic data were tracked using an electromagnetic system synced with motion analysis software. Peak and times-series joint angular velocities were tracked over the final 101 frames of the pitch. Pitch velocity was significantly correlated with peak elbow flexion (r =.380, p =.016) and wrist flexion (r =.621, p <.001) angular velocity. A small difference in elbow joint angular velocity was found between body fat percentage groups between ball release and follow-through (SPM(t)1,38 = 3.296, p =.003). Peak joint angular velocities are related to pitch velocity and slight differences in movement patterns exist according to pitcher body fat percentage.